Formulasi dan Evaluasi sediaan Handwash Emulgel dari Sari umbi Wortel (Daucus carota.) - adam mustapa, mohamad; aprianto paneo, mohamad; Uno, Wiwit Zuriati; Anggai, Rifka Anggraini; Olii, Zihan Maura Putri (Jurnal Literasi Mandiri, 2024)
Carrots are a vegetable that has health benefits. Carrot tubers contain saponin, besides that the leaves contain tannin and the tubers have an antibacterial effect against gram-positive and gram-negative bacteria. Flavonoids in carrot tubers are known to inhibit the bacteria Propionibacterium acne, Staphylococcus aureus, Escherichia coli. This research aims to determine the formulation and evaluation of carrot root juice (Daucus carota L.) in the form of emulgel hand washing soap, using experimental laboratory methods. This research began with optimizing the HPMC gel base to see the concentration of the gel base using three different concentration variations, namely (0.5%), (1%), and (1.5%), of these three concentrations HPMC produced the base. gel with good viscosity and clarity, namely 1%. Then the Handwash Emulgel preparation was formulated in one formula with an active substance concentration of (20%) and HPMC base (1%). Evaluation of the Handwash Emulgel preparation includes organoleptic tests (mint aroma, orange color, thick gel form), viscosity test gets 1400 Cp, pH test gets pH 7, homogeneity test gets homogeneous results, foam height test gets 30mm. The research results show that carrot root juice (Daucus carota L.) can be formulated as an active substance in making hand washing soap emulgel preparations.